2010
DOI: 10.5171/2010.458727
|View full text |Cite
|
Sign up to set email alerts
|

E-learning Barriers in the United Arab Emirates: Preliminary Results from an Empirical Investigation

Abstract: E-learning is relatively new to the United Arab Emirates. Most tertiary institutions have allocated ICT resources to provide alternatives to the previously used teacher-centred "chalk and talk" approach to learning and teaching. However we have not yet developed a comprehensive understanding of the application of elearning methods and resources in the tertiary education sector in the UAE. This paper describes a collaborative research project which empirically investigated the perceived barriers to e-learning f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Lack of ICT skills [1], [32], [16], [24], [17], [26], [28], [18], [19], [21] [22], [23] Lack of E-Learning knowledge [1], [17], [14], [31], [25] Instructors Resistance to change [33], [16], [16] [24], [34], [17], Lack of time to develop e-courses [2], [33], [16], [18], [21], [29], [22], [35], [30], [23], [25] Lack of Motivation [1], [17], [22], [35], [23] While getting the quantitative results through survey, it was also found in Table 6 that most of the respondents agreed about the importance of barrier factors of instructor dimension for successful implementation of E-Learning having mean in between 3.31 to 3.70. It can be concluded from the data in Table 6 that among all the respondents, "Lack of Time to Develop E-courses" is having the highest mean value (3.70).…”
Section: Resources / Referencesmentioning
confidence: 99%
“…Lack of ICT skills [1], [32], [16], [24], [17], [26], [28], [18], [19], [21] [22], [23] Lack of E-Learning knowledge [1], [17], [14], [31], [25] Instructors Resistance to change [33], [16], [16] [24], [34], [17], Lack of time to develop e-courses [2], [33], [16], [18], [21], [29], [22], [35], [30], [23], [25] Lack of Motivation [1], [17], [22], [35], [23] While getting the quantitative results through survey, it was also found in Table 6 that most of the respondents agreed about the importance of barrier factors of instructor dimension for successful implementation of E-Learning having mean in between 3.31 to 3.70. It can be concluded from the data in Table 6 that among all the respondents, "Lack of Time to Develop E-courses" is having the highest mean value (3.70).…”
Section: Resources / Referencesmentioning
confidence: 99%
“…These areas are: Information and communication technology (ICT) environment issues, student characteristics, support for students, and provision of authentic activities [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Martin et al, 2010;Mynard, 2003;Vrazalic, MacGregor, & Behl, 2009). A recent unpublished doctoral dissertation has reviewed information literacy experiences of Emirati tertiary students, and concluded that many students had difficulties accessing information, often due to difficulties with the English language, but also as a result of finding information which may not be relevant to their experiences (Johnston, 2013).…”
Section: Self-perceived Confidence Skill With Digital Technologiesmentioning
confidence: 99%